Yi yi a film by Edward Yang - Jin, Yanhing (Criterion Coll., 2006)
Follows a middle-class family in Taipei over the course of a year, from a wedding at the start to a funeral at its end.
Orig.:
Orig.: Taiwan/Japan, 2000
Aspect ratio, 16:9 widescreen. - New, restored high-definition digital transfer
Orig.:
Enth. Special features
Keywords: Families -- Taiwan -- Drama; Funeral rites and ceremonies -- Taiwan -- Taipei -- Drama; Middle class families -- Taiwan -- Taipei -- Drama; Weddings -- Taiwan -- Taipei -- Drama; Taipei (Taiwan) -- Drama; Feature films; Feature films - Japan; Feature films - Taiwan; Foreign language films - Chinese - Mandarin